Early pancreatic volume reduction on CT predicts relapse in patients with type 1 autoimmune pancreatitis treated with steroids - Ohno, Yoshinori (Orphanet J Rare Dis, 2016)
BACKGROUND: Type 1 autoimmune pancreatitis (AIP) is clinically characterized by a response to steroid therapy. Despite having a favorable prognosis, AIP has a high relapse rate and factors predicting relapse in AIP patients treated with steroids have not yet been established. METHODS: A retrospective chart review was conducted of 32 newly diagnosed type 1 AIP patients who had undergone enhanced computed tomography (CT) pre- and post-steroid therapy. RESULTS: Ten patients experienced relapse. Pancreatic volume was reduced significantly in all patients (pre-treatment volume, 88.5 ± 32.9 cm(3) vs. post-treatment volume, 45.4 ± 21.1 cm(3); P < 0.001), although the pre-treatment pancreatic volume did not differ between the relapse and non-relapse groups (92.6 ± 10.5 cm(3) vs. 86.6 ± 7.1 cm(3), P = 0.401). However, the post-treatment pancreatic volume was significantly greater in the relapse group than that in the non-relapse group (56.9 ± 6.3 cm(3) vs. 40.2 ± 4.2 cm(3), P = 0.008). Similarly, the percent reduction in pancreatic volume was significantly smaller in the relapse group than that in the non-relapse group (36.6 ± 4.7 % vs. 52.1 ± 3.2 %, P = 0.002). Multivariate analysis identified post-treatment pancreatic volume (HR, 1.04, 95 % CI: 1.01–1.08, P = 0.010) and percent reduction in pancreatic volume (HR, 0.87, 95 % CI: 0.79–0.94, P < 0.001) as predictive factors for relapse of type 1 AIP. A post-treatment pancreatic volume of 50 cm(3) < (P = 0.009) and a percent reduction in the pancreatic volume of <35 % (P = 0.004) had a significantly high relapse rate. These data suggest that early pancreatic volume changes after steroid therapy may be a useful prognostic value, because type 1 AIP patients with a high post-treatment pancreatic volume or low pancreatic volume reduction showed significant relapse. CONCLUSIONS: Early pancreatic volume reduction on CT after steroid therapy indicates the therapeutic effects of steroids, and a low decrease in the pancreatic volume may be associated with a limited response that predicts future relapse in patients with type 1 AIP. Reduction of steroids in these cases must be observed carefully with consideration of immunomodulator use.